Boolean query translation for multiple web information systems - Firdaus Othman (2008)
This research work explores the use of an alternative method to formulate query statements based on the Extensible Mark-up Language (XML) to query multiple Web Information Systems. The XML query statements formulated according the rules that are developed by this work and are processed accordingly to suit different informations but yet producing the same results.